Effects of Corneal Biomechanical Properties on Rebound Tonometry (Icare200) and Applanation Tonometry (Perkins) Readings in Patients With Primary Congenital Glaucoma. Issue 3 (March 2022) - Morales-Fernandez, Laura; Saenz-Frances, Federico; Pérez-García, Pilar; Garcia-Feijoo, Julian; Garcia-Saenz, Sofia; Gómez de Liaño, Rosario; Martinez-de-la-Casa, Jose M.
Abstract : Objective: The aim was to assess the influence of corneal biomechanics on intraocular pressure (IOP) measurements made with the Icare200 (IC200) rebound tonometer and the Perkins handheld applanation tonometer in patients with primary congenital glaucoma (PCG). Materials and Methods: A total of 40 PCG patients and 40 healthy controls, age, and sex-matched, were recruited. IOP was measured with the Ocular Response Analyzer (IOPc, IOPg), IC200 and Perkins. The variables age, IOP, corneal hysteresis (CH), corneal resistance factor (CRF), central corneal thickness (CCT), best-corrected visual acuity, spherical equivalent, medications, and glaucoma surgeries were recorded for each subject. Univariate and multivariate analysis were used to detect effects of variables on IOP measurements. Results: Mean CCT was 545.65±71.88 μm in PCG versus 558.78±27.58 μm in controls ( P =0.284). CH and CRF were significantly lower in PCG group than in control group: mean CH 8.11±1.69 versus 11.15±1.63 mm Hg ( P <0.001), and mean CRF 9.27±2.35 versus 10.71±1.75 mm Hg ( P =0.002). Mean differences between IOP IC200-Perkins were 0.79±0.53 mm Hg in PCG versus 0.80±0.23 mm Hg in controls ( P <0.001) and mean differences IC200-IOPc were −0.89±5.15 mm Hg in PCG ( P <0.001) versus 1.60±3.03 mm Hg in controls (all P <0.009). Through multivariate analysis, CRF showed positive association and CH negative association with IOP measured with Perkins or IC200 in both subject groups. No association was detected for CCT, age, or sex. Conclusion: CH and CRF were identified as the main factors interfering with IOP measurements made with both tonometers in patients with PCG and healthy controls.